2015
DOI: 10.1103/physrevb.91.014435
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties of FeRh alloys: The antiferromagnetic to ferromagnetic transition

Abstract: The electronic, magnetic, thermodynamical, and transport properties of FeRh alloys are studied from first principles. We present a unified approach to the phase stability, an estimate of exchange interactions in various magnetic phases, and transport properties including the effect of temperature which are all based on the same electronic-structure model. Emphasis is put on the transition between the ferromagnetic (FM) and antiferromagnetic (AFM) phases. Such a study is motivated by a recent suggestion of FeRh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 40 publications
7
36
0
1
Order By: Relevance
“…4(c)] whereas points correspond to experimental data taken from different authors indicated in the inset. The fitting to the experimental data renders the following estimations zJ = 5.66 meV and = 36 (Å) 3 , comparable to recently reported values for the exchange constant [61] and the lattice parameter [53], respectively. The misfit between theory and experiments (∼10% around the tricritical point) is partially due to the more attention given in the fitting procedure at the behavior close to P = 0.…”
Section: B Ferh Metamagnetic Alloysupporting
confidence: 87%
“…4(c)] whereas points correspond to experimental data taken from different authors indicated in the inset. The fitting to the experimental data renders the following estimations zJ = 5.66 meV and = 36 (Å) 3 , comparable to recently reported values for the exchange constant [61] and the lattice parameter [53], respectively. The misfit between theory and experiments (∼10% around the tricritical point) is partially due to the more attention given in the fitting procedure at the behavior close to P = 0.…”
Section: B Ferh Metamagnetic Alloysupporting
confidence: 87%
“…The overall gain in energy is very small and it is impossible to clearly separate the competing contributions. But we may speculate that the strong hybridization of rhodium and iron states in both the AF and the FM phase, responsible for both the implicit splitting of Rh in the AF phase and the evolution of a net magnetic moment in the FM phase [51,52], is also decisive for the structural stability of B2 FeRh. This could explain why rather different mechanisms such as increasing the local exchange splitting of Fe via constrained magnetic moments, or decreasing the band width by increasing the volume, or shifting the relative position of the elemental orbitals using the GGA+U approach, have the same consequence, i. e., stabilizing the B2(AF) phase.…”
Section: B Electronic Origin Of the Lattice Instabilitymentioning
confidence: 99%
“…There are a number of theoretical/computational models that can describe the ferromagnetic (FM) or antiferromagnetic (AFM) phase [25][26][27][28] and first-principles models can be used to understand the effects of interfaces and atomic termination [29]. The present approach allows for the simultaneous description of both the FM and the AFM phases using a single set of parameters, based on the atomistic spin dynamics formalism [30].…”
Section: A Numerical Modelmentioning
confidence: 99%